Modulating DDAH/NOS Pathway to Discover Vasoprotective Insulin Sensitizers. (6th December 2015) - Lai, Li; Ghebremariam, Yohannes T.
Abstract : Insulin resistance syndrome (IRS) is a configuration of cardiovascular risk factors involved in the development of metabolic disorders including type 2 diabetes mellitus. In addition to diet, age, socioeconomic, and environmental factors, genetic factors that impair insulin signaling are centrally involved in the development and exacerbation of IRS. Genetic and pharmacological studies have demonstrated that the nitric oxide (NO) synthase (NOS) genes are critically involved in the regulation of insulin-mediated glucose disposal. The generation of NO by the NOS enzymes is known to contribute to vascular homeostasis including insulin-mediated skeletal muscle vasodilation and insulin sensitivity. By contrast, excessive inhibition of NOS enzymes by exogenous or endogenous factors is associated with insulin resistance (IR). Asymmetric dimethylarginine (ADMA) is an endogenous molecule that competitively inhibits all the NOS enzymes and contributes to metabolic perturbations including IR. The concentration of ADMA in plasma and tissue is enzymatically regulated by dimethylarginine dimethylaminohydrolase (DDAH), a widely expressed enzyme in the cardiovascular system. In preclinical studies, overexpression of DDAH has been shown to reduce ADMA levels, improve vascular compliance, and increase insulin sensitivity. This review discusses the feasibility of the NOS/DDAH pathway as a novel target to develop vasoprotective insulin sensitizers.